Calnexin and calreticulin promote folding, delay oligomerization and suppress degradation of influenza hemagglutinin in microsomes. - Hebert, D N (1996)
Calnexin (CNX) and calreticulin (CRT) are molecular chaperones that bind preferentially to monoglucosylated trimming intermediates of glycoproteins in the endoplasmic reticulum. To determine their role in the maturation of newly synthesized glycoproteins, we analyzed the folding and trimerization of in vitro translated influenza hemagglutinin (HA) in canine pancreas microsomes under conditions in which HA's interactions with CNX and CRT could be manipulated. While CNX bound to all folding intermediates (IT1, IT2 and NT), CRT was found to associate preferentially with the earliest oxidative form (IT1). If HA's binding to CNX and CRT was inhibited using a glucosidase inhibitor, castanospermine (CST), the rate of disulfide formation and oligomerization was doubled but the overall efficiency of maturation of HA decreased due to aggregation and degradation. If, on the other hand, HA was arrested in CNX-CRT complexes, folding and trimerization were inhibited. This suggested that the action of CNX and CRT, like that of other chaperones, depended on an 'on-and-off' cycle. Taken together, these results indicated that CNX and CRT promote correct folding by inhibiting aggregation, preventing premature oxidation and oligomerization, and by suppressing degradation of incompletely folded glycopolypeptides.